Genetic Variation in HSD17B13 Reduces the Risk of Developing Cirrhosis and Hepatocellular Carcinoma in Alcohol Misusers - Stickel, Felix; Lutz, Philipp; Buch, Stephan; Nischalke, Hans Dieter; Silva, Ines; Rausch, Vanessa; Fischer, Janett; Weiss, Karl Heinz; Gotthardt, Daniel; Rosendahl, Jonas; Marot, Astrid; Elamly, Mona; et al. (Hepatology, 2020)
Background and Aims Carriage of rs738409:G in patatin-like phospholipase domain containing 3 (PNPLA3) is associated with an increased risk for developing alcohol-related cirrhosis and hepatocellular carcinoma (HCC). Recently, rs72613567:TA in hydroxysteroid 17-beta dehydrogenase 13 (HSD17B13) was shown to be associated with a reduced risk for developing alcohol-related liver disease and to attenuate the risk associated with carriage of PNPLA3 rs738409:G. This study explores the risk associations between these two genetic variants and the development of alcohol-related cirrhosis and HCC.
CRIS-Team WoS Importer:2020-06-02